Dynamics of ephemeral streams at the foot of degraded catchments in northern Ethiopia. (9th December 2019) - Demissie, Biadgilgn; Van Eetvelde, Veerle; Frankl, Amaury; Billi, Paolo; Asfaha, Tesfaalem G.; Haile, Mitiku; Nyssen, Jan
Abstract: The magnitudes of flash floods and their effect on channel width changes were investigated for Hara River in the Raya graben (northern Ethiopia). Precipitation was measured using rain gauges evenly distributed over the study catchment. Event peak discharges were measured with crest‐stage gauges at a reference cross‐section. Changes in channel width were measured at six monitoring sites along a 1.5 km long reach. Decadal channel width change was analyzed over the period 1965–2014. The average rainfall depth of the rainy days was 14.2 ± 9.4 mm whereas the highest was 41.9 mm and the lowest, capable to generate some flow in the river, was only 1.8 mm. The maximum calculated discharge peaked at 408 m 3 /s whereas the lowest flow was 19.5 m 3 /s. An average widening of 0.11 ± 0.19 m per flood (for a total of 3.74 m) was measured. The cumulative precipitation and cumulative channel widening suggest that larger and longer lasting rains have substantial influence on channel width change. A marked increase in channel width commonly accompanies 2–3 days of flood duration; it is less marked where there is riparian vegetation on the banks. The long‐term (1965, 1986, 2005, and 2010) measurements indicate that channel width increased rapidly over the last 50 years; nearly 25 m of widening. Generally, channel changes are mainly induced by the duration of floods rather than by their intensity and the data clearly show that ephemeral streams channel dynamics can be triggered also by floods much smaller than bankfull.